Cannabinoids, Medical Cannabis, and Colorectal Cancer Immunotherapy - Zaiachuk, Mariia; Pryimak, Nazar; Kovalchuk, Olga; Kovalchuk, Igor (Frontiers in Medicine, 2021)
Colorectal cancer is a major public health problem. Unfortunately, currently, no effective curative option exists for this type of malignancy. The most promising cancer treatment nowadays is immunotherapy which is also called biological or targeted therapy. This type of therapy boosts the patient's immune system ability to fight the malignant tumor. However, cancer cells may become resistant to immunotherapy and escape immune surveillance by obtaining genetic alterations. Therefore, new treatment strategies are required. In the recent decade, several reports suggest the effectiveness of cannabinoids and Cannabis sativa extracts for inhibiting cancer proliferation in vitro and in vivo, including intestinal malignancies. Cannabinoids were shown to modulate the pathways involved in cell proliferation, angiogenesis, programmed cell death and metastasis. Because of that, they are proposed as adjunct therapy for many malignancies. By far less information exists on the potential of the use of cannabis in combination with immunotherapy. Here, we explore the possibility of the use of cannabinoids for modulation of immunotherapy of colon cancer and discuss possible advantages and limitations.